Tinjauan Kebijakan Diskon Logam Mulia Dalam Upaya Meningkatkan Pendapatan Penjualan PT. Pegadaian UPC Cibadak - Anggraeni, Sherlyana; Sudarma, Ade (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to determine the mechanism of precious metal discount policy and what efforts have been made by PT. Pegadaian UPC Cibadak in increasing sales of precious metals. In the preparation of this study, the object of research researched by the author is discounts on the sale of precious metals at PT. Pawnshop UPC Cibadak. In this study, researchers used qualitative methods and descriptive approaches. The results showed that sales and revenue of precious metals increased during the discount period, in early January 2022 PT. Pegadaian UPC Cibadak sells precious metal products measuring 25 grams with sales revenue of Rp. 23,497,000, - and the most sales in September PT. UPC Cibadak pawnshop sold 201 grams and sales revenue of Rp. 160,720,000,-. This has a positive impact on PT. Pawnshop UPC Cibadak.